1978
DOI: 10.1139/x78-015
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistance related to phloem width in red maple

Abstract: Electrical resistances of combined bark and wood of 50 red maple (Acerrubrum L.) trees were strongly correlated with phloem width with an inverse correlation coefficient of −0.92. Diameter at 1.4 m aboveground was determined to be transitively correlated with electrical resistance through its strong correlation with phloem width. Little detectable relationship existed between electrical resistance and potassium concentration in phloem tissues. An electrical model is presented to illustrate the path of electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…SHORTLE et al (1977SHORTLE et al ( , 1979 showed that electrical resistance to a pulsed electric current in the cambial zone of sprout red maple, hybrid poplar, and sugar maple was inversely proportional to rate of growth. CARTER and BLANCHARD (1978) showed a high negative correlation between electrical resistance and phloem thickness in red maple, as did COLE and JENSEN (1979) in lodgepole pine. Together, these studies suggest that growth rate and hence, tree vigor, are related to bark thickness.…”
Section: Discussionmentioning
confidence: 88%
“…SHORTLE et al (1977SHORTLE et al ( , 1979 showed that electrical resistance to a pulsed electric current in the cambial zone of sprout red maple, hybrid poplar, and sugar maple was inversely proportional to rate of growth. CARTER and BLANCHARD (1978) showed a high negative correlation between electrical resistance and phloem thickness in red maple, as did COLE and JENSEN (1979) in lodgepole pine. Together, these studies suggest that growth rate and hence, tree vigor, are related to bark thickness.…”
Section: Discussionmentioning
confidence: 88%
“…Like Stamm (), we found that wood moisture content can supersede species identity as a determinant of electrical resistivity. Although the important role of moisture in wood resistivity is well established (Al Hagrey, ; Carter & Blanchard, ; Gora & Yanoviak, ), no other studies have compared moisture‐resistivity patterns among growth forms or trees in situ.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant correlation between average stand SER and several spectral indices. While SER could be correlated to stress conditions, others have cautioned (e.g., Newbanks andTattar 1977, Carter andBlanchard 1978) that several other factors, such as thermal variation and seasonal changes, can influence results. It is important, therefore, to ensure that changes in SER are a true reflection of stress-related effects.…”
Section: Individual Tree Assessmentsmentioning
confidence: 99%